Faktor Resiko Peningkatan Kolesterol pada Usia Diatas 30 Tahun di Kota Banda Aceh - Agus Hendra Al-Rahmad; Annaria Annaria; T. Khairul Fadjri (Poltekkes Kemenkes Yogyakarta, 2016)
Background: In the national of Population Aged >30 years is the highest percentage of obesity. Aceh has a percentage of 11.9% obese. The amount of it prevalence a very concern about the survival of society, especially those that living in Banda Aceh. The higher prevalence rate associated with cholesterol, and it can cause death. Objective:The aim of research to measure the risk factors of cholesterol elevated levels of people aged >30 years in Banda Aceh. Method: The research designed a case-control study be conducted in Banda Aceh city, the sample is people aged >30 years, and was cholesterol levels checks in Prodia laboratory as many as 60 sample. Collecting data through interviews and observations, with analysis used Chi-Square test on CI:95%. Results: Research results obtained by a relationship between the gender (p= 0,010, OR= 4,6), age (p= 0,034, OR= 3,8), descent (p= 0,036, OR= 3,6), BMI (p= 0,019, OR= 4,1) with elevated levels of cholesterol in the people aged >30 years in Banda Aceh. Conclusion: The nutritional status (BMI) and the gender factor has the greatest risk to increase in cholesterol levels. In conclusion, the risk its the gender, age, descent, and BMI. Known also proved a gender and BMI is the dominant predictor to increased cholesterol levels. Keywords: Cholesterol, risk factors, people aged >30 years